Kata Dapat Merugikan Keuangan Negara Dalam Undang-Undang Tindak Pidana Korupsi dan Undang-Undang Perbendaharaan Negara - Salmon, Harly Clifford Jonas (MATAKAO Corruption Law Review, 2023)
Introduction: The element of State Financial Loss in the Corruption Law as a formal offence where to prove the state financial loss whether the state lost or not, is not important but more emphasis on the potential financial loss of the state and the State Treasury Law as a material offence which emphasizes that the state financial loss must be proven and calculated. Purposes of the Research: Analysing the Elements of State Financial Loss in the Corruption Law and the State Treasury Law. Methods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials carried out in this research is through literature study, namely by searching legal materials by reading, seeing, listening, or now it is mainly done by searching via the internet. The data will be analyzed using quantitative data analysis techniques in a quantitative approach. Quantitative related to the relationship of variables is analyzed using an objective theory, then described to solve the main problem in this study. Results of the Research: the conclusions can be drawn as follows: The element "may harm state finances or the state economy" is a potential loss of state finances or the state economy, not only because the act is "detrimental to state finances or the state economy in real terms", but only "may" cause losses as a possibility or potential loss. The word "may" before the phrase "harming state finances or the state economy" indicates that the criminal offence of corruption is a formal offence, that is, the existence of a criminal offence of corruption is sufficient with the fulfilment of the elements of the formulated act, not with the occurrence of the consequences. With the formulation of the criminal offence of corruption as contained in Article 2 paragraph (1) and Article 3 of Law Number 31 Year 1999 as amended by Law Number 20 Year 2001 as a formal offence, the existence of losses to the state or the state economy does not have to have occurred, because what is meant by a formal offence is an offence that is considered to have been completed by the commission of an act prohibited and threatened with punishment by law. With the formulation of the criminal offence of corruption as a formal offence, the existence of state financial losses or losses to the state economy does not have to have occurred, because a formal offence is an offence that is considered to have been completed by the commission of a prohibited act and is threatened with punishment by law.